2012
DOI: 10.1590/s1413-78522012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Espondilolistese traumática do áxis: epidemiologia, conduta e evolução

Abstract: ObjectiveTo evaluate cases of traumatic spondylolisthesis of the axis and describe them in relation to epidemiology, classification, neurological deficit, healing time and treatment method.MethodA retrospective analysis of the medical records of patients treated between 2002 and 2010 at IOT-FMUSP. Inclusion criteria: pars interarticularis fracture of C2.Results68% were male patients, with a mean age of 39.1 years. We used the classification by Effendi, modified by Levine-Edwards. Type I fractures were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
16
1
Order By: Relevance
“…Other causes include fall from a height and rarely diving accidents. 2,4,21 Motor vehicle accidents were the sole cause of injury in our series of 32 patients. Whether a different mechanism of injury, with presence of rotational force, plays a role in our findings of high percentage of asymmetrical fractures, vertebral bodies and posterior elements involvement need to be confirmed by further studies.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Other causes include fall from a height and rarely diving accidents. 2,4,21 Motor vehicle accidents were the sole cause of injury in our series of 32 patients. Whether a different mechanism of injury, with presence of rotational force, plays a role in our findings of high percentage of asymmetrical fractures, vertebral bodies and posterior elements involvement need to be confirmed by further studies.…”
mentioning
confidence: 75%
“…2,5,12,21 This observation can be well explained by the fact that the central canal diameter at upper cervical region is wide and typically tends to expand following neural arch fracture. Neurological deficit due to cord injury was seen in only two patients in our series that was proven by MRI.…”
mentioning
confidence: 99%
“… 2 Most authors define hangman's fracture as bilateral fractures of the pars interarticularis. 3 4 5 6 7 …”
Section: Introductionmentioning
confidence: 99%
“…As a result of the unremarkable C2/3 intervertebral disc, no ventral approach was considered. Several studies showed good results with different strategies of conservative treatment with halo fixation, a cervical collar, or a Minerva cast [ 10 12 ]. ElMiligui et al described contrary results with nonunion, instability, or persistent pain [ 13 ].…”
Section: Discussionmentioning
confidence: 99%